Debaryomyces hansenii F39A as biosorbent for textile dye removal - Ruscasso, Maria Florencia; Bezus, Brenda; Garmendia, Gabriela; Vero, Silvana; Curutchet, Gustavo Andres; Cavello, Ivana Alejandra; Cavalitto, Sebastian Fernando (Revista Argentina de Microbiología)
Many industries generate a considerable amount of wastewater containing toxic and recalcitrant dyes. The main objective of this research was to examine the biosorption capacity of Reactive Blue 19 and Reactive Red 141 by the Antarctic yeast Debaryomyces hansenii F39A biomass. Some variables, including pH, dye concentration, amount of adsorbent and contact time, were studied. The equilibrium sorption capacity of the biomass increased with increasing initial dye concentration up to 350 mg/l. Experimental isotherms fit the Langmuir model and the maximum uptake capacity (qmax) for the selected dyes was in the range of 0.0676?0.169 mmol/g biomass. At an initial dye concentration of 100 mg/l, 2 g/l biomass loading and 20 ± 1 °C, D. hansenii F39A adsorbed around 90% of Reactive Red 141 and 50% of Reactive Blue 19 at pH 6.0. When biomass loading was increased (6 g/l), the uptake reached up to 90% for Reactive Blue 19. The dye uptake process followed a pseudo-second-order kinetics for each dye system. As seen throughout this research study, D. hansenii has the potential to efficiently and effectively remove dyes in a biosorption process and may be an alternative to other costly materials.ResumenMuchas industrias generan un gran volumen de aguas residuales que contienen colorantes, los cuales son compuestos tóxicos y recalcitrantes. El objetivo principal de este estudio fue examinar la capacidad bioadsortiva de la biomasa de la levadura antártica Debaryomyces hansenii F39A, en presencia de los colorantes azul reactivo 19 y rojo reactivo 141. Se estudiaron algunas variables del proceso, incluyendo el pH, la concentración de colorante y de adsorbente utilizada y el tiempo de contacto. La capacidad de adsorción se incrementó al aumentar la concentración del adsorbato hasta 350 mg/L. Los datos de las isotermas obtenidas experimentalmente se ajustaron con el modelo de Langmuir, donde la capacidad máxima de adsorción (Qmáx) para ambos colorantes se encuentra dentro del rango 0,0676-0,169 mmol/g de biomasa. A una concentración ...